Probiotic Consortia: Reshaping the Rhizospheric Microbiome and Its Role in Suppressing Root-Rot Disease of Panax notoginseng - Zhang, Jinhao; Wei, Lanfang; Yang, Jun; Ahmed, Waqar; Wang, Yating; Fu, Lina; Ji, Guanghai (Frontiers in Microbiology, 2020)
Root-rot disease caused by Fusarium oxysporoum is a growing problem in agriculture for commercial cultivation of Panax notoginseng. Diverse microbes colonize plant roots, and numerous earlier studies have characterized the rhizospheric microbiome of P. notoginseng, still the function of probiotic consortia on the rhizospheric microbiome against the root-rot disease remain elusive. We compare and describe the rhizospheric microbiome of light diseased and severe diseased P. notoginseng, the interactions of probiotic consortia and rhizospheric microbiome, and their function to alleviate the plant diseases were explored by inoculating probiotic consortia in bulk soil. From the perspective of microbial diversity, the rhizospheric dominant bacterial and fungal genera were utterly different between light and over-serious diseased plants. Through inoculating assembled probiotic consortia to diseased plant roots, we found that the application of probiotic consortia reshaping the rhizosphere microbiome, increasing the relative abundance of bacteria and fungi, while the relative abundance of potential pathogens was decreased significantly. We developed a microcosm system that provides a preliminary ecological framework for constructing an active probiotic community to reshape soil microbiota and restrain the disease. Microbial community structure is different between light and over-serious diseased plants. The application of probiotic consortia changes the imbalance of micro-ecology to the state of relative health and reducing plant mortality. Plant disease suppression may be achieved by seeking and applying antagonistic microbes based on their direct inhibitory capability or restructures the soil microbiome structure and function.